Pengaruh Strategi Coping terhadap Risiko Kambuh Klien Badan Narkotika Nasional: Peran Persepsi Diri sebagai Variabel Moderasi - Silvia Fitri; Suwarjo Suwarjo (Universitas Muhammadiyah Metro, 2026)
Drug abuse is a significant health and social challenge. Relapse prevention is a key aspect of the recovery process. This quantitative study aims to examine the role of coping strategies (problem-focused and emotion-focused) and self-perception of relapse risk among 215 clients undergoing rehabilitation at the National Narcotics Agency (BNN) in Central Java and Yogyakarta provinces. Using an explanatory approach, data were collected through a Likert scale and analyzed using moderation regression with the bootstrapping method to address the issue of data non-normality. The results of the study produced surprising findings: contrary to the theoretical framework, both types of coping strategies (problem-focused and emotion-focused) were found to have a positive and significant effect on increasing the risk of relapse. This indicates that the intensity of coping strategy use is correlated with higher relapse vulnerability. Similarly, self-perception was found to have a positive and significant effect on relapse risk, indicating that unrealistic or overly optimistic self-perceptions may be a risk factor in this population. Furthermore, self-perception was not found to significantly moderate the relationship between coping strategies and relapse risk. Overall, these findings highlight that the coping strategies and self-perception present in BNN clients are likely to be maladaptive or unsupported by practical skills, so that factors that theoretically function as protectors actually act as predictors of relapse risk.